Characteristics and genetic model of dolomite reservoirs in the Qigebulak Formation, Upper Sinian, Tarim Basin, China - Li, Zongfeng; Bao, Zhidong; Su, Yuchi; Ban, Shuyue; Li, Yilin; Wang, Tengyu; Tao, Ye; Wei, Mingyng; Lu, Kai (Frontiers in Earth Science, 2025)
In recent years, oil and gas exploration has expanded into ultra-deep fields. Thick primary dolomite is developed in the Qigebulak Formation of the Tarim Basin, but there is little research on the petrological characteristics and reservoir genetic mechanisms of the primary dolomite. The Qigebulak Formation consists of the upper, middle, and lower members, and the dolomite can be divided into crystalline dolomite, grain dolomite, and algal framework dolomite. The analysis of the petrological and geochemical characteristics shows that dolomites in the middle member retain the geochemical characteristics of the original deposition. The δ13C of member Ⅱ ranges from 3.2‰ to 4.6‰ (VPDB), and δ18O range from −1.7‰ to 2.1‰ (VPDB). These values are consistent with the distribution range of carbon and oxygen isotopes in seawater during deposition. The REE distribution patterns of the three members of the Qigebulak Formation are relatively flat and right-inclined, with REE < 100 ppm. The LREE/HREE ratio ranges from 6.34 to 23.83, with an average of 13.82, indicating LREE enrichment and HREE relative loss. Overall, the dolomite in the Qigebulak Formation is formed by seawater deposition. Sedimentation is the foundation and premise of reservoir development. Effective reservoirs are mainly developed in the grain banks and microbial mounds, with the reservoir spaces mainly consisting of algal framework pores and intergranular pores. Supergene karstification plays a key role in the formation of the reservoir, and the upper Qigebulak Formation experienced strong surface dissolution. During the burial stage, high temperature and high pressure caused the source rocks of the Yuertusi Formation to dissolve and form organic acidic fluids. The dissolution of these acidic fluids promoted the improvement of the reservoir’s physical properties. Based on a comprehensive analysis of the controlling factors for reservoir development, a reservoir genetic model is established. The primary pores are developed in early sedimentary microbial mounds and grain banks, serving as the foundation for reservoir development. During the Late Sinian period, influenced by the Keping movement, the Tarim Basin experienced tectonic uplift, leading to extensive supergene karst development under the influence of meteoric water. In the burial phase, the degradation of organic matter produced acidic fluids that dissolved dolomite, thereby further enhancing porosity. The dolomite reservoir of the Qigebulak Formation developed under the control of sedimentation, supergene dissolution, and burial dissolution. At present, industrial oil and gas have been discovered in the Sinian system in the Tabei Region, but the overall exploration level is low. The well-developed paleokarst reservoirs suggest that the Sinian system holds promise for oil and gas exploration.